Collaborative management partnerships strongly decreased deforestation in the most at-risk protected areas in Africa since 2000 - Sébastien Desbureaux; Ibrahim Kabore; Giulia Vaglietti; Mujon Baghai; Peter Lindsey; Ashley Robson; Philippe Delacote; Antoine Leblois (Proceedings of the National Academy of Sciences, 2025)
Collaborative management partnerships (CMPs) between state wildlife authorities and nonprofit conservation organizations to manage protected areas (PAs) have been used increasingly across Sub-Saharan Africa since the 2000s. They aim to attract funding, build capacity, and increase the environmental effectiveness of PAs. Our study documents the rise of CMPs, examines their current extent, and measures their effectiveness in protecting habitats. We combine statistical matching and Before-After-Control-Intervention regressions to quantify the impact of CMPs, using tree cover loss as a proxy. We identify 127 CMPs located in 16 countries. CMPs are more often located in remote PAs, with habitats that are least threatened by human activity. Our results indicate that, on average, each year in a CMP results in an annual decrease in tree cover loss of about 55% compared to PAs without CMPs. Where initial anthropogenic pressure was low, we measure no effect. Where it was high, we see a 66% decrease in tree cover loss. This highly heterogeneous effect illustrates the importance of moving beyond average effect size when assessing conservation interventions, as well as the need for policy makers to invest public funds to protect the areas the most at risk.